Pembatalan Hasil PILKADES Menurut Peraturan Perundang-Undangan - Hendrik Ruben Gelong (Jurnal Ilmu Hukum Kanturuna Wolio, 2021)
This study aims to determine the mechanism for the cancellation of the results of the Village Head election that canoccur in Lawela Village, Batauga District, Sounth Buton Regency. And to find out objectively what factors are related to the cancellation of the election results for the Head of Lawela Village, Batauga District, Sounth Buton Regency. This research is qualitative and descriptive analysis, with the type of research used in this study is juridical normative in other words, namely by harmonizing and describing the real situation regarding a problem that occurs by combining materials from books and related laws and regulations. In addition, in thie study the authors conducted direct interviews with the parties concerned to complete each data. The research location is in Lawela Village, Batauga District, Sounth Buton Regency. Types and sources of data using primary data and secondary data. Data collection techniques using field studies and literature studies. The result showed that the cancellation of the results of the Lawela Village Head election was not in accordance with the procedure, therefore the Village Heas who was entitled to be elected did not raise any objections to the South Buton Regent after the determination of the results of the Lawela Village Head election as intended South Buton Regent Regulation Number 23 of 2019 concerning Head Election. Village as referred to in Article 53. Based on the official report on theresults of the Vote Count result for the Lawela Head Election which was also attended by the Village Head Candidate and the Village Head Candidate witnesses, ther was no record of any Special Events and / or objections of the candidates.